Explain the problems of Abu Tammam poetry For Abu Hamed Ahmed bin Mohammed Al-Bashti Kharzenji, who died in 348 AH: -Section Three- - Salman, Nabil Mohammed (Al-Adab Journal, 2021)
This is the third and final section of the book (Explanation of the problems of Abu Tamam's poetry) by Abu Hamed Ahmed bin Mohammed Al-Bashti Al-Kharaznji (d. 348 AH). May Allah make it easier for me to publish the first and second sections. Section We have collected what we have lost from this important book mentioned by the books of literary criticism of ancient and pointed to its importance in explaining the Court of Abu Tammam and interpretation.In this way, we have served our glorious Arab heritage and the revival of the loss of it to the extent that it has facilitated us, including an addition to the scholars of the Abbasid poetry in general and Abu Tammam's poetry in particular.Our last prayer is that Praise be to Allah, Lord of the Worlds, that he is the Lord and yes